Análise comparativa entre estudantes oriundos de colégios agrícolas e outras escolas no curso de Agronomia da Universidade Federal de Santa Maria - Wolff, Roberto L.; Tonini, Enio (Revista do Centro de Ciências Rurais, 2008)
Realizou-se uma análise comparativa do desempenho entre um grupo de 140 Engenheiros Agrônomos, oriundos de Escolas Agrícolas, corn outro grupo de 227 Engenheiros Agrônomos oriundos de outras escolas de segundo grau, no concurso vestibular e ao longo dos oito semestres do curso. Os dois grupos analisados concluiram seus cursos no período compreendido entre 1971 e 1974. Apesar de se verificar diferenças significativas entre as médias, somente, a partir do quinto semestre, e favorável ao grupo oriundo de Escolas Agrícolas, as seguintes tendências foram evidenciadas: - Estudantes oriundos de Escolas Agricolas apresentaram a média ligeiramente inferior aos estudantes oriundos de outras escolas no concurso vestibular. - Estudantes oriundos de Escolas Agrícolas apresentaram média superior aos oriundos de outras escolas em todos semestres do curso, sendo que no 5º, 7º e 8º semestre a diferença foi significativa a nível de 5%. - A percentagem de alunos que necessitaram mais de oito semestres para completar o curso foi de 8,57% para oriundos de Escolas Agrícolas, e 13,65% para oriundos de outras escolas. - A média geral das notas obtidas de ambos os grupos tende a aumentar do 1º ao 8º semestre. - A variação na distribuição das médias tende a diminuir à medida que os estudantes de ambos os grupos se aproximam do final do cursoAbstract In an analysis of the performance of a group of 140 Engenheiro Agronomo students from Agricultural Colegios in comparrison to a group of 227 Engenheiro Agronomo students from 2nd level schools other than agricultural colegios revealed that there were some significant differences in the performance as measured by mean scores of the vastibular and eight (8) semestres of course works at the UFSM. The two groups that were under investigation graduatet in 1971, 1972, 1973 and 1974 respectively. Although significant differences were found only in course works during the 5th 7th and 8th semestres as measured by the difference in mean values at the 05 per cent confidence level, the following tedencies are evident: - Students from the Agricultural Colegios scored slightly lower on the vestibular than students from other 2nd level schools. - Students from the Agricultural Colegios scored slightly higher in course works each semester than students from other and level schools and were found to score significanty higher at the 05 confidence level at the end of the 5th and 7th and 8th semesters during which time the course load was the gratest and number of credits in technical agricultural courses were taken. - More student from the Agricultural Colegios completed their course of study in the planned eight semester program in comparrison to students from other and level schools. - Students from both groups tend to score progressively better grades from the 1st through the 8th semester. - The variation of grade distribuition of both groups tends to decrease as students progress in their course work from the 1st through the 8th semester.